How important is obesity as a risk factor for respiratory failure, intensive care admission and death in hospitalised COVID-19 patients? Results from a single Italian centre. Issue 4 (October 2020) - Rottoli, Matteo; Bernante, Paolo; Belvedere, Angela; Balsamo, Francesca; Garelli, Silvia; Giannella, Maddalena; Cascavilla, Alessandra; Tedeschi, Sara; Ianniruberto, Stefano; Rosselli Del Turco, Elena; Tonetti, Tommaso; Ranieri, Vito Marco; et al.
Abstract : Objective: : Specific comorbidities and old age create a greater vulnerability to severe Coronavirus Disease 19 (COVID-19). While obesity seems to aggravate the course of disease, the actual impact of the BMI and the cutoff which increases illness severity are still under investigation. The aim of the study was to analyze whether the BMI represented a risk factor for respiratory failure, admission to the intensive care unit (ICU) and death. Research design and methods: : A retrospective cohort study of 482 consecutive COVID-19 patients hospitalised between March 1 and April 20, 2020. Logistic regression analysis and Cox proportion Hazard models including demographic characteristics and comorbidities were carried out to predict the endpoints within 30 days from the onset of symptoms. Results: : Of 482 patients, 104 (21.6%) had a BMI ≥ 30 kg/m 2 . At logistic regression analysis, a BMI between 30 and 34.9 kg/m 2 significantly increased the risk of respiratory failure (OR: 2.32; 95% CI: 1.31–4.09, P = 0.004) and admission to the ICU (OR: 4.96; 95% CI: 2.53–9.74, P < 0.001). A significantly higher risk of death was observed in patients with a BMI ≥ 35 kg/m 2 (OR: 12.1; 95% CI: 3.25–45.1, P < 0.001). Conclusions: : Obesity is a strong, independent risk factor for respiratory failure, admission to the ICU and death among COVID-19 patients. A BMI ≥ 30 kg/m 2 identifies a population of patients at high risk for severe illness, whereas a BMI ≥ 35 kg/m 2 dramatically increases the risk of death.